MUSLIM COMMUNAL POLITICS AND PARTITION OF INDIA: IMPERIALIST AND CAMBRIDGE HISTORIOGRAPHY - Singh, Amarjit (European Scientific Journal, ESJ, 2013)
The Imperialist and Cambridge historiography on the Muslim Communal politics and partition of India and on the political changes among the Muslims of colonial India tend to fall into five separate categories. The historians of the first category are of the opinion that the omissions, tactical errors and diplomatic blunders on the part of the Indian National Congress changed the Muslim politics and led to the growth of the Muslim Communal politics subsequently resulting in the form of the partition of India. The second category of these historians are of the opinion that the forces of the colonial policy and the constitutional measures adopted by the colonial state helped to the emergence and growth of the Muslim communal politics and led to the partition of India. It has been suggested by the third category of these scholars that the growth of the Muslim separatism in India was manipulated and determined by the Muslim elites at the national and provincial level whose propaganda based on communal identification was responded to the Muslims of colonial India. The historians of the fourth category have argued that although the colonial policy and its evolution of the representative from of the government led to the emergence and consolidation of the Muslim communal politics but the demand of a separate Muslim state was not the design of Muslims of India. It has been viewed by the scholars of the fifth category that the Muslim separatism in colonial India and the partition of India was the result of the interplay between the three major political players i.e., the British, the Indian National Congress and the All India Muslim League and that the partition of India was a first major act of decolonization.